Teacher Strategies In Managing Digital-Based Learning - Abd Rahman Lasindrang; Warni Tune Sumar; Sulkifly Sulkifly (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to describe teachers' strategies in managing digital-based learning at SDN 90 Sipatana, Gorontalo City. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions, while the validity of the data is tested through triangulation of sources and techniques. The results of the study indicate that teachers' strategies in managing learning at SDN are implemented through three main stages, namely planning, implementation, and evaluation of learning integrated with the use of digital technology. In the planning stage, teachers prepare learning by referring to the Learning Outcomes (CP) in the Independent Curriculum. In this process, teachers utilize digital platforms such as Canva to design interesting teaching media, as well as YouTube as a reference source for learning materials. In the implementation stage, teachers apply flexible learning by adjusting to the conditions and needs of students. The strategy used involves the use of various digital media, especially learning videos from YouTube to help understand concepts visually. In addition, teachers also use technological devices such as laptops, LCD (projectors) and PID (Digital Interactive Boards) to increase student interaction and involvement in the learning process. Meanwhile, the evaluation of digital-based varied and adapted to student needs. learning at SDN 90 Sipatana was carried out through various forms of assessment that The assessment sued included digital-based interactive quizzes. The research findings show that teacher strategies are able to create interactive, adaptive, and student-centered learning despite limited infrastructure.